Estudo inicial de combustível anelar para PWR - Raphael Henrique Martins Silva (2017)
The generation of electric energy through thermonuclear process has contributed effectively to the increasing energy demand. According to the IAEA (International Atomic Energy Agency), currently more than half of commercial reactors in operation in the world are of type PWR (Pressurized Water Reactor), which use fuels rods in the form of cylindrical pellets of uranium oxide (UO2). This geometry has been maintained for many years; However, several studies have been developed using fuels in annular fuel rods. This work aims to evaluate the replacement of traditional rods of a typical PWR 16 x 16 fuel assembly arrangements for annular fuel rods. So, a set of computer simulations were performed to calculate parameters neutronics of ECAs (Advanced Assemblies) and to compare the results with ECP (Standard Assembly). In this context, the MCNPX 2.6.0 (Monte Carlo N-Particle eXtended) code was used to simulate the ECAs 13 x 13, 14 x 14 and 15 x 15 arrangements and the ECP typical PWR 16 x 16 arrangement. The external dimensions of the ECP and the VM/VF (Moderator Volume / Fuel Volume) were kept equal in all simulated assemblies. The enrichment of fuel was 3.2% to the ECP 16, 3.8% to ECA 13 and 3.9% to ECAs 14 and 15. The different values of enrichment of annular settings were determined to obtain the same kinf of standard assembly. The infinite multiplication factor, neutronic flux, peaking factor, axial and radial power distribution were calculated by the MCNPX 2.6.0. Futhermore, the evolution of the fuel was evaluated during the burnup. After all simulations have performed, both annular fuel assemblies ECA 14 (3.9%) and ECA 15 (3.9%), were conducive to incorporation of annular geometry in your configuration. Neutronics parameters as power distribution, flux, criticality and burnup demonstrate similar behaviors between ECAs and confirm the equivalence of results. The continuity of research directs the other compositions of fuels, enrichment and thermo-hydraulic analysis in simulations of ECAs, aiming to acquire more accurate parameters for determining the configuration of ECA to be used in possible replacements in the core.